Distribuição espacial das estações de rádio base no município de Fortaleza - Pereira, Eduardo Campos (2015)
The growing demand for mobile telephony services and the advent of new technologies requires their continued expansion, in order to ensure safe, reliable and high quality to its users. As a direct consequence of this growth has been the need to increase the amount of Radio Base Stations (RBS) to be installed. This expansion may have visual impacts and damage to the health of the population in the surrounding areas of the base stations, seeking always the best practices for the deployment of base stations. This model is based on policies that allow for expansion of services of mobile networks and, at the same time reduce the visual impact of these facilities as well as damage to the health of the surrounding area of the population, in a complementary manner to the applicable legislation. This concern is motivated by the loss of quality of service presented by the mobile operators, due especially to the poor distribution of antenna signal distributors. The objective of this work is to make a diagnosis of the spatial distribution of Radio Base Stations in the city of Fortaleza, focusing on its normative aspects and the current management system and supervision of those cell sites. The technical and regulatory aspects of installations of base stations used in mobile telephony will be searched, focusing the case study in Fortaleza, in addition to identifying the public agencies responsible for managing the inspection of cell sites in this municipality, and establish their respective responsibilities. For this, the methodology used in the study is based on qualitative exploratory research, using the deductive method of approach, performing literature, through the consultation of books, periodicals, theses, dissertations and legislation available on mobile telephony in Brazil and world, its normative aspects and criteria for installation of base stations. Also we used a field survey, through structured interviews managers of public agencies responsible for the management and supervision of RBS. The study showed that Fortaleza has 843 base stations registered by ANATEL (2014), with 6.8 million active mobile lines. Research by the SEUMA showed, among other aspects, despite the demands of municipal law in 8914, supervising or is done randomly, or from accusations of \\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\"disagreement\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\\" made by the people and that the body responsible not talk to one itself.